2021
DOI: 10.3389/fphar.2021.682020
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Pharmacogenomics Testing Among Physicians, Pharmacists, and Researchers From China

Abstract: To elucidate current domestic factors influencing pharmacogenomics (PGx) implementation and its future in China, we conducted a questionnaire survey on PGx applications and testing. A questionnaire-based survey was created on the popular online professional survey platform “Wenjuanxing” (www.wjx.cn) and performed via the social media platform WeChat. Among 422 participants, there were physicians (27.7%), pharmacists (31.3%), and researchers (41.0%). We found that less than 50% of physicians were aware of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…It is worth mentioning that although PGx research has been advanced rapidly in recent years, the clinical implementation of PGx has a long way to go (Guo et al, 2021). To reduce HDMTXrelated toxicities and improve outcomes, in addition to the role of genetic polymorphisms, renal function evaluation prior to treatment, co-medications, hydration and urinary alkalization, therapeutic drug monitoring (TDM), and leucovorin rescue might be taken into full consideration.…”
Section: Recommendation For Clinical Practicementioning
confidence: 99%
“…It is worth mentioning that although PGx research has been advanced rapidly in recent years, the clinical implementation of PGx has a long way to go (Guo et al, 2021). To reduce HDMTXrelated toxicities and improve outcomes, in addition to the role of genetic polymorphisms, renal function evaluation prior to treatment, co-medications, hydration and urinary alkalization, therapeutic drug monitoring (TDM), and leucovorin rescue might be taken into full consideration.…”
Section: Recommendation For Clinical Practicementioning
confidence: 99%
“…Given that our results showed that respondents’ understanding of domestic guidelines and expert consensus was better than their knowledge of the three well-known international standard guidelines or databases (CPIC, PharmGKB, ClinGen), the lack of domestic guidelines might have impacted the uptake of PGx testing. Likewise, Guo and colleagues [ 13 ] conducted a survey on PGx use among physicians, pharmacists, and researchers and found that over 50% of pharmacists recognized the importance of PGx testing. However, the pharmacists also perceived that the lack of clinical studies and domestic guidelines were the main barriers to increasing uptake of PGx testing, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, pharmacists in high-income countries reported limited knowledge of and many concerns about PGx; high costs, limited insurance reimbursement, lack of domestic clinical guidelines, lack of trust in the vendor of PGx results, and fear of discrimination and misinterpretation of test results were among factors commonly recognized to have hindered PGx’s uptake in clinical practices [ 12 ]. In 2019, Guo et al [ 13 ] designed a questionnaire to obtain a comprehensive understanding of PGx by physicians, pharmacists, and researchers. However, given its small sample size of pharmacists and the fact that the respondents mainly resided in south-central and south-western regions, such as Hunan Province, and did not distinguish between types of pharmacists, there is a lack of research on the clinical pharmacists’ knowledge of and attitudes toward PGx in China.…”
Section: Introductionmentioning
confidence: 99%
“…Our study shows that HLA-B PGx testing has been increasing tremendously for the past 10 years in our lab. The general reasons could be the emerging sequencing technologies which shrinking the cost of sequencing ( Schwarze et al, 2018 ), the better understanding or awareness about PGx application among health care professional especially among physician, and availability of standard international and national guideline on the clinical utility of PGx testing ( Guo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%